Evaluation of sperm quality in successive regular collections from captive black-and-gold howler monkeys (Alouatta caraya) - Carvalho, F. M. [UNESP]; Arakaki, P. R.; Nichi, M.; Muniz, J. A.P.C.; Duarte, J. M.B. [UNESP]; Valle, R. R. (My University, 2014)
The black-and-gold howler monkey serves as a suitable model for development of assisted reproductive techniques (ARTs), which may later be applied in threatened species of the same genus. The objectives of this study were to evaluate semen characteristics of black-and-gold howler monkeys (Alouatta caraya), with emphasis on mitochondrial activity and acrosome integrity, using staining methods that are suitable for use under field conditions. Twenty six semen samples were collected by rectal probe electroejaculation from six adult captive males from the National Primate Center (CENP), Ananindeua, PA, Brazil. The following parameters were evaluated in each semen sample: volume, pH, concentration, plasma membrane integrity, acrosome integrity, and mitochondrial activity. Both Spermac stain and the Simple Staining Method were suitable for acrosome evaluation. Diaminobenzidine needs further investigation to improve its application for this species. Overall semen quality improved from the first collection to the fifth collection. This highlights the importance of repeating semen collections when evaluating a male for use in ARTs. This research brought novel information on semen characteristics of Alouatta caraya which will aid further studies on the application of ARTs in this and other primate species.
Keywords: Acrosome integrity; Diaminobenzidine; Mitochondrial activity; Semen; Simple staining method